Rest-mediated regulation of extracellular matrix is crucial for neural development. - Yuh-Man Sun; Megan Cooper; Sophie Finch; Hsuan-Hwai Lin; Zhou-Feng Chen; Brenda P Williams; Noel J Buckley (PLoS ONE, 2008)
Neural development from blastocysts is strictly controlled by intricate transcriptional programmes that initiate the down-regulation of pluripotent genes, Oct4, Nanog and Rex1 in blastocysts followed by up-regulation of lineage-specific genes as neural development proceeds. Here, we demonstrate that the expression pattern of the transcription factor Rest mirrors those of pluripotent genes during neural development from embryonic stem (ES) cells and an early abrogation of Rest in ES cells using a combination of gene targeting and RNAi approaches causes defects in this process. Specifically, Rest ablation does not alter ES cell pluripotency, but impedes the production of Nestin(+) neural stem cells, neural progenitor cells and neurons, and results in defective adhesion, decrease in cell proliferation, increase in cell death and neuronal phenotypic defects typified by a reduction in migration and neurite elaboration. We also show that these Rest-null phenotypes are due to the dysregulation of its direct or indirect target genes, Lama1, Lamb1, Lamc1 and Lama2 and that these aberrant phenotypes can be rescued by laminins.